Race and Retention in a Competitive Labor Market: The Role of Historically Black Colleges and Universities in NCAA Basketball. (April 2018) - LaFave, Daniel; Nelson, Randy; Doherty, Michael
Between 1994 and 2013, Black head coaches of Division I National Collegiate Athletic Association basketball programs were more likely to be terminated than their White counterparts, adjusting for performance and characteristics of the coach. Controlling for employment at a historically Black college or university, which accounts for approximately a quarter of the Black coaches in our sample, overturns this result. The findings highlight the importance of understanding institutional environments when assessing discrimination in labor market outcomes.